Who will mind the baby? : geographies of child care and working mothers - England, Kim, 1960- (London ; New York : Routledge, 1996)
One of the most significant social and economic changes in recent years has been the explosion in the number of mothers in the work place and in paid employment generally. Child care policy, provision and funding has in no way kept up with this change. Who Will Mind the Baby? explores how working mothers negotiate their responsibilities in the face of these difficulties.
Child care arrangements greatly influence the everyday geographies of working mothers. A wealth of case studies - drawn from the national, regional, rural, metropolitan and local levels - illustrates the real impact of these arrangements on working mothers. The book contrasts the limited child care policies of the United States and Canada with the more advanced situation in Europe and Australia, focusing in particular on the coping strategies of working mothers.
1. Who Will Mind the Baby? / Kim England -- 2. Minding the Baby in the United States / David E. Bloom and Todd P. Steen -- 3. Minding the Baby in Canada / Marie Truelove -- 4. Making the Transition to School: Which communities provide full-day public kindergarten? / Ellen K. Cromley -- 5. Child Care Services in Ontario: Service availability in a decentralized provision system / Ian Skelton -- 6. The Journey to Child Care in a Rural American Setting / Holly J. Myers-Jones and Susan R. Brooker-Gross -- 7. The Locational Context of Child Care Centers in Metropolitan Toronto / Marie Truelove -- 8. Mothers, Wives, Workers: The everyday lives of working mothers / Kim England -- 9. Mother or Worker?: Women's support networks, local knowledge and informal child care strategies / Isabel Dyck -- 10. The State and Child Care: An international review from a geographical perspective / Ruth Fincher -- 11. Conclusion / Kim England.
Includes bibliographical references and index.
Keywords: Child care -- Government policy; Child care services -- United States; Child care services -- Canada